A numerical study on MM-NEMO scheme: impact of rising number of mobile routers and cell residence time - Islam, Shayla; Hassan Abdalla Hashim, Aisha; Habaebi, Mohamed Hadi; Hassan, Wan Haslina; Abdul Latif, Suhaimi; Hasan, Mohammad Kamrul; Mohd. Ramli, Huda Adibah (Springer Verlag, 2015)
Signaling overhead is a significant issue for mobile network due to increase traffic load with packet loss and delay during frequent movement of Mobile Router (MR) from one subnet to another in Network Mobility Basic Support protocol (NEMO BSP). Accordingly, advance preparation mechanism (i.e. Fast Hierarchical Mobile IPv6) works very well as a node mobility solution in order to solve these matters. Yet, combining this host-based protocol for macro mobility handoff in NEMO environment is a challenging issue as both MR and its Mobile Network Nodes (MNNs) must be taken into consideration. In this paper, a numerical framework is developed to study the total handoff cost of Macro Mobility scheme in NEMO (MM-NEMO). The numerical results confirms that MM-NEMO scheme outperforms the standard NEMO BSP relat-ed to total handoff delay cost (51% less than that of NEMO-BSP) regardless of increasing the number of MRs as well as cell residence time.